2020
DOI: 10.1016/j.hedp.2020.100814
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of plasma detachment in the magnetic thrust chamber using full particle-in-cell simulation

Abstract: A magnetic nozzle, which is a convergent-divergent magnetic field to control a plasma flow, has been investigated for application to plasma propulsion systems in spaceships. In the magnetic nozzle, plasma thermal energy is converted to one-directional kinetic energy by Lorentz force to generate thrust. Although magnetic field structure and strength are optimized for improvement of the thrust performance, it is essential to understand physical processes of plasma ejection from the nozzle, because the plasma may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Numerical models for the magnetized plasma plume expansion through a magnetic nozzle are of different types. A first approach is that of the kinetic approaches, which can be split into methods solving a simplified Boltzmann's equation for the ion and electron distribution functions in a low dimensional space (typically 1D, [18]), and full particle-incell (PIC) models [19,20], featuring particle ions/electrons, collisions through Montecarlo approaches [21], and generally limited to 2D to reduce the computational cost. An alternative approach, which is computationally cheaper, is that of hybrid codes, in which electrons are modeled as a fluid, while neutrals and ions are followed as macro-particles of a PIC sub-model featuring Montecarlo collisions.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical models for the magnetized plasma plume expansion through a magnetic nozzle are of different types. A first approach is that of the kinetic approaches, which can be split into methods solving a simplified Boltzmann's equation for the ion and electron distribution functions in a low dimensional space (typically 1D, [18]), and full particle-incell (PIC) models [19,20], featuring particle ions/electrons, collisions through Montecarlo approaches [21], and generally limited to 2D to reduce the computational cost. An alternative approach, which is computationally cheaper, is that of hybrid codes, in which electrons are modeled as a fluid, while neutrals and ions are followed as macro-particles of a PIC sub-model featuring Montecarlo collisions.…”
Section: Introductionmentioning
confidence: 99%
“…They made the electrostatic assumption and derived a self-similar scaling law to reduce computation time. Kojima et al used a collisionless PIC code to investigate plasma detachment from a magnetic nozzle [100]. They found that ion demagnetisation led to ion detachment, but in order to study electron detachment their code must be modelled on a larger spatial scale.…”
Section: Particle-in-cellmentioning
confidence: 99%
“…In a stream of work parallel to the directed study of the AF-MPDT and HET, there has been considerable effort to study the impact of a magnetic nozzle on the flow of plasma from a plasma source, particularly in the past 15 years [122] [123] [100]. There has been a concerted effort to develop a theory of plasma within a magnetic nozzle, where a simplified plasma source model is assumed and all efforts are concentrated into how the plasma interacts with the nozzle itself [124].…”
Section: Notable Studies On Magnetic Nozzlesmentioning
confidence: 99%